Advancing nearshore wave monitoring: estimating parameters through video time stack imagery - Chintam Venkateswarlu; Baggu Gireesh; Madipally Ramesh; Surisetty VV ArunKumar; Chennu V. Naidu; Leela Sheela Nair; Rashmi Sharma (Ocean Dynamics, 2025)

Strategic on-demand combat against preformed mature bacterial biofilms using a sustainable and flexible chia mucilage-based triboelectric nanogenerator - Karthikeyani Ramesh; Sasirekha Venkidusamy; Monica Ramasamy; Rajeswari Murugesan; Arunkumar Chandrasekhar; Jeyanthinath Mayandi (Chemical Engineering Journal, 2025)

The genetic architecture of tristyly and its breakdown to self‐fertilization - Ramesh Arunkumar; Wei Wang; Stephen I. Wright; Spencer C. H. Barrett (Molecular Ecology, 2017)
The floral polymorphism tristyly involves three style morphs with a reciprocal arrangement of stigma and anther heights governed by two diallelic loci ( S and M ). Tristyly functions to promote cross‐pollination, but modifications to stamen position commonly cause transitions to selfing. Here, we integrate whole‐genome sequencing and genetic mapping to investigate the genetic architecture of the M locus and the genetic basis of independent transitions to selfing in tristylous Eichhornia paniculata . We crossed independently derived semi‐homostylous selfing variants of the long‐ and mid‐styled morph fixed for alternate alleles at the M locus ( ssmm and ssMM , respectively), and backcrossed the F 1 to the parental ssmm genotype. We phenotyped and genotyped 462 backcross progeny using 1450 genotyping‐by‐sequencing (GBS) markers and performed composite interval mapping to identify quantitative trait loci (QTL) governing style‐length and anther‐height variation. A QTL associated with the primary style‐morph differences (style length and anther height) mapped to linkage group 5 and spanned ~13–27.5 Mbp of assembled sequence. Bulk segregant analysis identified 334 genes containing SNPs potentially linked to the M locus. The stamen modifications characterizing each selfing variant were governed by loci on different linkage groups. Our results provide an important step towards identifying the M locus and demonstrate that transitions to selfing have originated by independent sets of mating‐system modifier genes unlinked to the M locus, a pattern inconsistent with a recombinational origin of selfing variants at a putative supergene.